Multimodal mass and social media messages. A comparative case study - Loewe, Iwona (Papers in Linguistics, 2023)
The methodological background of the article is media linguistics along with the multimodal analysis method. The subject of research is a fragment of the media discourse on the arrival of Novak Djoković to Melbourne for the tennis tournament and the related events between January 4 and 11, 2022. The compared multimodal content and the obtained results allow for the conclusion that messages from the mass and new media effectively created the media image of the event and profiled the content in accordance with the common and established knowledge about the tennis player Djoković and strengthened the stereotypes about him and the Serbs. The use of prosumer media consists in communication practices that are capable of producing and sustaining discursive images of an event or person for a long time. For these users, Djoković performs various social roles. Social media can be an extension of mass media with respect to reinforcing media images of the world. Commonalities between these images are the production, structure and distribution techniques. Differences are usually the values and the beliefs, emotions, knowledge and effects associated with them.